Potret Kenakalan Santri di Pondok Pesantren: Analisis Faktor, Bentuk dan Upaya Penanggulangannya - Ahmad Zainul Abidin; Muhammad Akmansyah; Amirudin Amirudin (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
Islamic boarding schools are actually a place to educate the character of students, but they are also inseparable from the existence of delinquency at their age. Delinquency cannot be left alone, but requires a special policy to overcome it. Al-Hidayah Keputran Islamic Boarding School has implemented policies in dealing with student delinquency, but there are still cases of delinquency committed by students. The purpose of this study is to reveal the forms, factors, and role of Islamic boarding schools in overcoming it. This research is qualitative in nature, where the primary data sources are the leaders of the Islamic boarding school, teachers and students, and the secondary data are books and documents. The data collection tool uses interview, observation and documentation methods. The results of this study indicate that in terms of dealing with student delinquency, several policies are always applied so that students can comply with Islamic boarding school regulations and policies are adjusted to the forms of delinquency that occur, most of which are delinquency that violates the applicable rules. The results of the efforts made by the al-Hidayah Keputran Islamic boarding school in dealing with student delinquency were 80% successful where this was shown by the deterrent effect and the nature of discipline and making students who violated better, this was due to the students' fear of the consequences of the violations committed.